Anticipation in the Structure of the Solving Problems Skill - Veselina Ivanova; Maria Temnikova (European Scientific Journal, ESJ, 2019)
In the study the accent is put on the significant role of the foreseeing in the heuristic aspects of the solving problems activity. Theoretical formulations are deduced and the possibility of its purposeful formation is well-founded on the basis of the developing training particularities by the solving problems process. In order to attain the goal the following methods are used: content analysis, pedagogical observation, pedagogical experiment, method of the determination of a success standard and a correlation degree. The obtained results of the theoretical and experimental work are directed to the integration with the intellectual development of children and pupils.